2007
DOI: 10.1002/chem.200601568
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Interaction with Prion Peptide Fragments Encompassing Histidine Residues Within and Outside the Octarepeat Domain: Speciation, Stability Constants and Binding Details

Abstract: A 31-mer polypeptide, which encompasses residues 84-114 of human prion protein HuPrP(84-114) and contains three histidyl residues, namely one from the octarepeat (His85) and two histidyl residues from outside the octarepeat region (His96 and His111), and its mutants with two histidyl residues HuPrP(84-114)His85Ala, HuPrP(84-114) His96Ala, HuPrP(84-114)His111Ala and HuPrP(91-115) have been synthesised and their Cu2+ complexes studied by potentiometric and spectroscopic (UV/Vis, CD, EPR, ESI-MS) techniques. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 56 publications
0
60
0
Order By: Relevance
“…[67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated. A comparison of the thermodynamic stabilities of the histidinecontaining fragments revealed that the peptides that encompass the amino acid sequences outside the octarepeat domain are even more efficient chelators of copper(II) than the single octarepeat fragments.…”
Section: Introductionmentioning
confidence: 71%
“…[67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated. A comparison of the thermodynamic stabilities of the histidinecontaining fragments revealed that the peptides that encompass the amino acid sequences outside the octarepeat domain are even more efficient chelators of copper(II) than the single octarepeat fragments.…”
Section: Introductionmentioning
confidence: 71%
“…Although the protonation processes of L 1 are strongly overlapped, the first three pK values are mostly related to deprotonation of the imidazole rings, while pK 4 , pK 5 also increases the acidity of imidazolium rings.…”
Section: Protonation Of the Ligandsmentioning
confidence: 99%
“…Linear peptides have long since been used to mimic the metal binding sites of metalloproteins [1][2][3][4][5][6][7] and metalloenzymes. [8][9][10][11][12] Previously, we also studied some histidine-rich peptides in order to create similar metal ion environment to native enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Such metal binding sites are obviously difficult to mimic by small peptides. However, a number of proteins possess relatively short histidine-rich sequences with strong metal binding ability, which substantially contributes to the function of the given macromolecule [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Beside the well known human serum albumin (HSA) [1], probably the prion proteins (PrP) [2] are the most studied examples of such sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the well known human serum albumin (HSA) [1], probably the prion proteins (PrP) [2] are the most studied examples of such sequences. Studies on the metal ion binding of peptides related to the N-terminal of HSA [3][4][5], and those mimicking the octarepeat region of PrP [6][7][8] demonstrated the usefulness of such studies. Besides, several peptides copying the putative metal binding sequences of e.g.…”
Section: Introductionmentioning
confidence: 99%